Enhancing nutrition and ending poverty: IFPRI and India - International Food Policy Research Institute (International Food Policy Research Institute, 2018)
IFPRI’S PARTNERSHIP WITH INDIA BEGAN MORE THAN 40 YEARS AGO, IN THE WAKE OF THE GREEN REVOLUTION. Over the last four decades, IFPRI’s research in India has addressed the most pressing issues of the times. In the late 1970s, as food production in India stagnated and the population grew, the IFPRI-India working relationship focused on technology and rural development. In the 1980s, IFPRI delved deeply into India’s agriculture sector—on issues such as foodgrain production, subsidies, dairy development, and livestock demand—while in the 1990s IFPRI’s work focused on such topics as public expenditure and poverty in rural India and incentives and constraints in the transformation of Indian agriculture. Research since the 2000s has expanded to include nutrition, public investment, climate change, value chains, capacity strengthening, and biofortification. IFPRI receives critical financial and logistical support from the Government of India, especially through the Indian Council of Agricultural Research and the Department of Agricultural Research and Education, and works alongside numerous research partners in the country. This brochure highlights some of the key collaborations between IFPRI and our Indian partners.